Pelatihan Teknik Aseptik Pencampuran Sediaan Steril di RS Efarina Pangkalan Kerinci: The Training of Aseptic Dispensing Technique for Sterile Preparations at Efarina Hospital, Pangkalan Kerinci - Sumule, Arsiaty; Oktadiana, Isma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Pharmacy is part of the health service that is oriented towards patient service, providing quality and affordable medicines for all levels of society. Patients deserve to receive comprehensive clinical pharmacy services, one of which is through dispensing sterile preparations. To avoid contamination when mixing sterile preparations, personnel need to apply aseptic techniques. Therefore, pharmacists need to receive regular training to improve their knowledge and skills in ensuring the quality of service. Thus, patient safety can be guaranteed. The purpose of this community service is to improve pharmacists’ skills in carrying out aseptic techniques for dispensing sterile preparations at Efarina Hospital, Pangkalan Kerinci. This training consists of several series including presentation through lectures, giving modules to participants, showing videos and practice, learning evaluation through pre-tests and post-tests, and training evaluation. There was an increase in the average pre-test score of 62.2 and the average post-test score of 81.4. The evaluation of the activity received a good response from the participants and they hoped that there would be a continuation of the training program with various topics. Community service was carried out well and proven effective in increasing the knowledge of pharmacists at Efarina Hospital, Pangkalan Kerinci regarding aseptic dispensing techniques for sterile preparations.